The Association between Blunt Cardiac Injury and Isolated Sternal Fracture - Anahita Dua; Jason McMaster; Pathik J. Desai; Sapan S. Desai; SreyRam Kuy; Maggy Mata; Jamie Cooper (Cardiology Research and Practice)
The treatment of isolated sternal fractures (ISF) throughout the world is heterogeneous. This study aimed to identify the incidence, morbidity, and mortality associated with isolated fractures of the sternum and describe current practice for diagnosis and management of ISF and cardiac injury at a level I trauma center in the UK. A retrospective cohort study of adult patients (>16 years) with ISF presenting from 2006 to 2010 was conducted. Eighty-eight patients with ISF were identified. Most patients (88%, 77) were admitted to hospital with 66% (58) of them discharged within 48 hours. Two (2%) patients had an ER EKG with abnormality but both resolved to normal sinus rhythm within 6 hours of follow-up. Serum CEs were drawn from 55 (63%) patients with only 2 (2%) having a rise in serum troponin >0.04; however, in both of these patients troponin quickly normalized. Six (7%) patients underwent echocardiograms without significant findings. In all 88 patients with ISF, no cases of clinically significant cardiac injury were identified. Patients presenting with an isolated sternal fracture with no changes on EKG or chest X-ray do not warrant an admission to hospital and may be discharged from the ER.